Optimisation of phytoremediation of zinc ion by Lemnaceae using response surface methodology - Tai Jia Wei; Pang Yean Ling; Lim Steven; Chong Woon Chan (E3S Web of Conferences)
Phytoremediation, an eco-friendly approach, offers a green pathway towards cleaner and safer water resources. The efficiency of zinc ion removal through phytoremediation by Lemnaceae as a function of Lemnaceae species, the mass of duckweed and the initial zinc ion concentration was studied. The central composite design was applied for surface response modelling to analyse the effects of the combination of environmental factors and optimise the phytoremediation process. The model achieved a satisfactory prediction with a coefficient of determination (R2) of 0.985 based on a modified quadratic model for the optimised phytoremediation process. Furthermore, the analysis of variance (ANOVA) was conducted to assess the adequacy and significance of the generated model. The optimal zinc ion removal of 88 % could be achieved by Spirodela polyrhiza, Wolffia arrhiza and Lemna minor at the initial zinc ion concentration of 92.92 mg/L, 39.5 mg/L, and 21.08 mg/L and duckweed mass of 22.56 g, 22.38 g, and 24.81 g under the exposure of ambient conditions with sufficient daylight exposure.